How digital converges cross-media news typologies across countries: a comparative study of news consumption in Estonia and Portugal - Kõuts-Klemm, Ragne (2017)
In this article we argue for the relevance of the internet in the convergence of news consumption in cross-country research in Estonia and Portugal. Being different in their histories and media systems, the comparative research revealed similarities in people’s news repertoires in the two countries, which led to interesting conclusions about the changes in audiences’ news universes. In comparing the repertoires special attention was given to online journalism content: why people use this content, how they evaluate the credibility of the news, and how they make sense of their news selections. The results show that online news repertoires are converging across the two countries, especially in repertoires where consumers are focused on the quality of news, but also to some extent in cases where they mostly got news from social media.